Growth‐phase dependent morphological alteration in higher plant thylakoid is accompanied by changes in both photodamage and repair rates. Issue 4 (17th April 2021) - Nozue, Hatsumi; Shigarami, Takashi; Fukuda, Shinji; Chino, Takayuki; Saruta, Ryouta; Shirai, Kana; Nozue, Masayuki; Kumazaki, Shigeichi
Abstract: Thylakoid membranes of young leaves consist of grana and stroma lamellae (stroma‐grana [SG] structure). The SG thylakoid is gradually converted into isolated grana (IG), almost lacking the stroma lamellae during growth. This morphological alteration was found to cause a reduction in maximum photosynthetic rate and an enhancement of photoinhibition in photosystem II (PSII). In situ microspectrometric measurements of chlorophyll fluorescence in individual chloroplasts suggested an increase of the PSII/PSI ratio in IG thylakoids of mature leaves. Western blot analysis of isolated IG thylakoids showed relative increases in some PSII components, including the core protein (D1) and light‐harvesting components CP24 and Lhcb2. Notably, a nonphotochemical quenching‐related factor in the PSII supercomplex, PsbS, decreased by 40%. Changes in the high light response of PSII were detected through parameters of pulse‐amplitude modulation fluorometry. Chlorophyll fluorescence lifetime indicated an increase of fluorescence quantum yield in IG. A minimal photodamage‐repair rate analysis on a lincomycin treatment of the leaves indicated that repair rate constant of IG is slower than that of SG, while photodamage rate of IG is higher than that of SG. These results suggest that IG thylakoids are relatively sensitive to high light, which is not only due to a higher photodamage rate caused by some rearrangements of PS complexes, but also to the retarded PSII repair that may result from the lack of stroma lamellae. The IG thylakoids found among many plant species thus seem to be an adaptive form to low light environments, although their physiological roles still remain unclear.